Impact of Genomic Variation of NFE2L2 (rs6706649) on Serum Glyoxalase-1 Levels in A Sample of Iraqi Type 2 Diabetic Patients with Retinopathy - Sarah Hashim Mhaibes; Shatha H Ali (Iraqi Journal of Pharmaceutical Sciences, 2025)
Nuclear factor erythroid-2-related factor-2 (NFE2L-2) is one important endogenous anti -oxidative stress signal pathway. Single nucleotide polymorphism (SNP) or genetic variants of NFE2L-2 may be accountable for the genesis of diabetic retinopathy. Glyoxalase-1 (Glo-1) is the rate-limiting enzyme in the detoxification of methylglyoxal (MG) into D-lactate. The activity of GLO1 is regulated by the transcription factor NFE2L2.The goal of this study is to ascertain whether there is an association between the rs6706649 of NFE2L2 gene variant with serum GLO-1 levels in a group of Iraqi diabetic patients diagnosed with diabetic retinopathy (DR). This study included ninety patients diagnosed with type 2 diabetes mellitus (48 females and 42 males), with ages ranging from 40 to 80 years. The participants were partitioned into two the following groups: Group A; 60 patients with type 2 diabetes mellitus diagnosed with DR (among them 29 patients with non-proliferative diabetic retinopathy (NPDR) and 31 patients with proliferative diabetic retinopathy (PDR)) and Group B: 30 patients without evidence of DR (DWR) considered as a control group were enrolled in the study. A non-significant difference in genotyping and allele carriage frequencies of rs6706649 (G/A) SNP between DR and DWR groups. Also, there was a non-significant difference between PDR and NPDR patients’ groups in relation to the different genotypes and alleles of rs6706649 (G/A) of NFE2L2 gene. However, the changing from the wild genotype (GG) to mutant (AA) and heretogynotypes (GA) had significant positive correlation with the increased serum levels of GLO-1 and significant negative correlation with serum level of methylglyoxal (MG) in patients with diabetic retinopathy. Furthermore, pentosidine, carboxymethyl lysine (CML), GLO-1 and MG levels were significantly higher in DR when compared to DWR groups. The A mutant allele of rs6706649 (G >A) had significant positive correlation with the increased serum GLO-1 levels in DR group. Meanwhile, DR group had increased serum MG, GLO-1, pentosidine and CML levels. Hence, these biomarkers can serve as prognostic indicators for diabetic retinopathy.